2009
DOI: 10.1371/journal.pone.0008225
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Blocks the Protective Expression of Nrf2/ARE Pathway in Peripheral Mononuclear Cells of Young Heavy Smokers Favouring Inflammation

Abstract: Cigarette smoking is an important risk factor for atherosclerosis, a chronic inflammatory disease. However the underlying factors of this effect are unclear. It has been hypothesized that water-soluble components of cigarette smoke can directly promote oxidative stress in vasculature and blood cells. Aim of this study was to study the relationship between oxidative stress and inflammation in a group of young smokers. To do this we evaluated: 1) the oxidation products of phospholipids (oxPAPC) in peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 37 publications
9
65
1
Order By: Relevance
“…Previous studies have demonstrated that OxPLs induce NRF2 and electrophilic genes ( 3,18,19 ). However, the mechanisms of activation are only partially understood.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that OxPLs induce NRF2 and electrophilic genes ( 3,18,19 ). However, the mechanisms of activation are only partially understood.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 KO mice have a tendency to develop age-dependent autoimmune and inflammatory lesions in multiple tissues (37,38). Inflammation is commonly observed in chemically induced pathology with Nrf2 deficiency (91)(92)(93)(94)(95)(96). Many ARE inducers are potent anti-inflammatory agents, and their potency for induction of ARE genes correlates well with their potency for inhibition of inflammation (97)(98)(99).…”
Section: Inflammation and Inflammasome Signalingmentioning
confidence: 99%
“…Free radicals and oxidants present in cigarette smoke, as well as endogenously produced oxidants and radicals (resulting from the smoke chemicalinduced alteration in the cellular redox system), cause a prooxidative environment. 20 This general shift is likely to contribute to lipid oxidation and to a general increase in oxidative modification (and inactivation) of biomolecules. Morrow et al 21 reported increased presence of lipid peroxidation products in the serum of smokers, and Salonen et al 22 found increased levels of circulating autoantibodies against oxidized LDL.…”
mentioning
confidence: 99%